Long-term evaluation of home-based pulmonary rehabilitation in patients with fibrotic idiopathic interstitial pneumonias. Issue 2 (8th April 2019) - Wallaert, Benoit; Duthoit, Louise; Drumez, Elodie; Behal, Hélène; Wemeau, Lidwine; Chenivesse, Cécile; Grosbois, Jean-Marie
Background: Few studies have examined the benefits of pulmonary rehabilitation in patients with fibrotic idiopathic pulmonary pneumonia (f-IIP). Here, we report the results of an observational study in routine clinical practice of home-based pulmonary rehabilitation for f-IIP patients. Methods: A total of 112 consecutive patients (61 with idiopathic pulmonary fibrosis and 51 with fibrotic nonspecific interstitial pneumonitis) were enrolled, of whom 65 had mild-to-moderate disease (forced vital capacity (FVC) ≥50% predicted and diffusing capacity of the lung for carbon monoxide ( D LCO ) ≥30% predicted) and 47 had severe disease (FVC <50% predicted and/or D LCO <30% predicted). The 2-month pulmonary rehabilitation programme consisted of a once-weekly visit with retraining, therapeutic education and psychosocial support. Patients were provided with an individualised action plan and were followed-up bimonthly for 12 months. Exercise tolerance (6-min stepper test (6MST)), mood (Hospital Anxiety and Depression Scale (HADS)) and quality of life (QoL) (Visual Simplified Respiratory Questionnaire (VSRQ)) were assessed before (T0 ), immediately after (T2 ), 6 months after (T8 ) and 12 months after (T14 ) the end of the pulmonary rehabilitation programme. Results: 6MST strokes, HADS Anxiety score and VSRQ score were each significantly improved at T2 (n=101), T8 (n=76) and T14 (n=62) compared with T0 values. The improvements in outcomes were not influenced by disease severity or subtype. Patients who completed the study had significantly better baseline FVC and D LCO values than those who did not. Conclusions: Home-based pulmonary rehabilitation provides long-term benefits in exercise tolerance, anxiety and QoL for patients with f-IIP. Pulmonary rehabilitation should be prescribed systematically as part of the therapeutic arsenal for these patients. This 12-month follow-up study shows that home-based pulmonary rehabilitation (PR) provides long-term benefits for patients with fibrotic idiopathic interstitial pneumonias. Home-based PR offers an alternative to in-hospital or outpatient PR programmes. http://ow.ly/JVdw30nSOYz